2021
DOI: 10.3389/fimmu.2021.677879
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants on Multiple Sclerosis: A Review of In Vitro and In Vivo Models

Abstract: BackgroundIncreased prevalence of depression has been observed among patients with multiple sclerosis (MS) and correlated with the elevated levels of proinflammatory cytokines and the overall deregulation of monoaminergic neurotransmitters that these patients exhibit. Antidepressants have proved effective not only in treating depression comorbid to MS, but also in alleviating numerous MS symptoms and even minimizing stress-related relapses. Therefore, these agents could prospectively prove beneficial as a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 101 publications
1
16
0
Order By: Relevance
“…In addition, there is no data on the effect of treatment with fluoxetine on immune response in patients with MS. Nevertheless, the results of our study correspond to the data from other studies in vivo and in vitro, confirming the anti-inflammatory effect of fluoxetine in autoimmune diseases (3,5). In particular, similar effects of treatment with SSRIs was observed in rheumatoid arthritis and psoriasis (3).…”
Section: The Influence Of Fluoxetine On Relapsing-remitting Ms Coursesupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, there is no data on the effect of treatment with fluoxetine on immune response in patients with MS. Nevertheless, the results of our study correspond to the data from other studies in vivo and in vitro, confirming the anti-inflammatory effect of fluoxetine in autoimmune diseases (3,5). In particular, similar effects of treatment with SSRIs was observed in rheumatoid arthritis and psoriasis (3).…”
Section: The Influence Of Fluoxetine On Relapsing-remitting Ms Coursesupporting
confidence: 91%
“…In this regard, much attention is drawn to the potential ability to inhibit neuroinflammation by treatment with serotonergic drugs. In vitro and in vivo studies have shown that selective serotonin reuptake inhibitors (SSRIs) can reduce EAE and MS severity (5). However, the immune mechanism of the anti-inflammatory effect of SSRIs on MS pathogenesis needs further study.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study in the United States ( Boeschoten et al, 2017 ) revealed 20.6% of MS patients suffered from depression. A significant factor responsible for MS relapses is stressful life events ( Brown et al, 2005 ; Stamoula et al, 2021 ). From a clinical point of view, it is therefore recommended to monitor psychological constructs such as depression, anxiety, and stress in pwMS ( Glaser et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability of immune cells to produce catecholamines has been demonstrated, suggesting the possible autoregulation by activating dopaminergic and noradrenergic receptors. Finally, biogenic amines’ involvement in MS pathogenesis is confirmed by the influence of serotoninergic and dopaminergic drugs on experimental encephalomyelitis (EAE) and MS course and the impact of disease-modifying therapeutics (DMT) of MS on the production of catecholamines by the immune cells [ 2 , 3 , 4 ]. In line with these data, the repurposing of dopaminergic, noradrenergic, and serotoninergic therapeutics as additional pathogenetic treatments in MS is discussed [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%